Утворення та використання вторинних енергоресурсів в Україні - Kuts G.O.; Litinska L.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
The state of formation and use of combustible and thermal secondary energy resources (SER) at the enterprises of energy-intensive industry branches for 2010 and 2015–2017 is considered. The analysis of indices of the SER output and use showed a significant decrease in the level of their utilization during these years. For example, the share of combustible SER utilization to the gross consumption of primary fuel in the energy balance was reduced by a factor of 2.18 in 2017 as compared with 2010 (from 8648.5 thousand tons of reference fuel in 2010 to 3961.7 in 2017) and thermal SER use to the delivery of thermal energy by heat generating sources of district heating system reduced by a factor of 3.15 (from 10,518.4 thousand GCal to 3339.5). This decline of the level of RES utilization is caused by a significant decrease in the production of leading energy-intensive industries of Ukraine and many obsolete and physically worn-out heat recovery units (HRU) at their enterprises, as far as the HRU fleet has not been replenished with new HRUs during recent years due to the lack of engineering base in the country for their manufacture. The increase in the level of SER utilization in the future will be determined by the development and structural reconstruction of the country's economy and the creation of a mechanical-engineering base for the production of utilization equipment for different industries, which are the main sources of SER output.